Laminate veneers phenomena: Esthetics above biology and function? - Diamantino, Pedro Santos [UNESP]; De Andrade, Guilherme Schmitt [UNESP]; Diamantino, Mariana Gadelho Gimenez [UNESP]; Francci, Carlos Eduardo; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Tribst, João Paulo Mendes (Wroclaw Medical University, 2025)
Indirect laminate veneers can deliver excellent esthetic results, but their use must remain secondary to biological and functional principles, requiring an ethical and evidence-based approach during treatment planning.